Emergence of gyrovirus 3 in commercial broiler chickens with transmissible viral proventriculitis. Issue 5 (20th June 2018) - Li, Gen; Yuan, Shiyu; He, Menglian; Zhao, Manda; Hao, Xiaojing; Song, Minxun; Zhang, Lingjuan; Qiao, Changming; Huang, Libo; Zhang, Li; Li, Chengui; Wang, Guihua; et al.
Abstract: Gyrovirus 3 (GyV3) has been identified in faeces from children with acute gastroenteritis. However, whether GyV3 is prevalent in poultry has not been determined to date. To the best of our knowledge, this study is the first to isolate GyV3 from commercial broiler chickens with transmissible viral proventriculitis (TVP) in China. The complete genome of the virus shares 98.4% sequence identity with the FecGy strain that causes acute gastroenteritis in children. Epidemiological investigation from 2013 to 2017 revealed that the infection rate of GyV3 reached 12.5% (42/336) in commercial broiler chickens with TVP, indicating that the infection of GyV3 was ubiquitous in chickens. The emergence of GyV3 in commercial broiler chickens should be highly concerning for public health.